Struktur Keluarga Jepang Kontemporer dalam Tiga Novel Karya Ogawa Yoko - Devi, Rima (Lingua Cultura, 2014)
Ogawa Yoko as a Japanese novelist mostly features the life of contemporary Japanese society in her novels. One that stands out from her works is the image of the Japanese family structure. Ogawa outlines the Japanese family structure in contrast to the Japanese family structure in actual society, as in the novel Kifunjin A No Sosei, Hakase No Aishita Suushiki, and Miina No Koushin. These three novels depict Japanese family structure more complex than her other novels. How Ogawa described Japanese family structure in the three novels is the issue on this article. This article is a literature study; data were collected from the three novels and analyzed using sociological literature approach and the concept of Japanese traditional family known as ie system. This paper shows that there was an implementation of the ie system in the three novels yet it was only a part of the ie concept.